Junior High School Students' Conceptual Understanding of Prerequisite Material in Solving SPLDV Questions in View of Students' Cognitive Style - Anastasya Bella Putri Tambunan; Dwi Priyo Utomo; Rizal Dian Azmi (Mathematics Education Journal, 2023)
Understanding of students' mathematical concepts plays a very important role as a factor to support learning activities. In studying a concept students must understand previous mathematical material as a prerequisite material. Students' conceptual understanding of a material can be influenced by several factors, one of them is the cognitive style factor that has different for each student. Different cognitive styles can be seen from the field independent and field dependent cognitive styles. The importance of understanding students' mathematical concepts of a material that is influenced by students' cognitive styles, it is necessary to analyze students' understanding of mathematical concepts. This qualitative research aims to determine students' conceptual understanding of the prerequisite material and its relationship with students' cognitive styles, and the ways students use in solving existing problems. The results in this study showed there was a significant relationship between the cognitive style of each student and the understanding of mathematical concepts towards the prerequisite material. This is because the field independent cognitive style has a good level of conceptual understanding while the field dependent cognitive style has a low level of conceptual understanding, because they have different levels of conceptual understanding so each student has their own way to solve existing problems.